Psychological Contract Fulfillment and Attitude towards Organizational Change: A Mediation and Moderation Analysis of Affective Commitment and Empowering Leadership - Edosomwan, Henry Samuel; Nwanzu, Chiyem Lucky (SEISENSE Journal of Management, 2021)
Purpose: The underlying factors connecting psychological contract fulfillment (PCF) to attitude towards organizational change (ATOC) have not received much attention in organizational behavior literature. Hence, this study examined the mediating role of affective commitment (AC) and the moderating role of empowering leadership (EL) in the relationship between PCF and ATOC among employees in private organizations. Design/Methodology: This is a quantitative cross-sectional survey. Systematic sampling was utilized for collecting data from employees in private organizations in Delta State, Nigeria, via standardized self-report measures. The sample consisted of 224 employees with a mean age of 28.56 and a standard deviation of 6.41. Regression analysis (Model 1 and 4 of Hayes PROCESS Macro) was used for testing the hypotheses through IBM SPSS version 26. Findings: The results showed that PCF and AC were positive and significant predictors of ATOC. The results also revealed a significant mediating effect of AC and a moderating effect of EL in the relationship between PCF and ATOC. Practical Implications: Human resources management (HRM) in private organizations should promote practices that enhance employees' attachment to the organization. Also, top managerial staff should be encouraged to practice empowering leadership because it promotes positive workplace behaviors. Originality/Value: The present study enhances and brings new critical knowledge regarding the mediating role of AC and the moderating role of EL in the relationship between PCF and ATOC.